1999
DOI: 10.1002/(sici)1520-6343(1999)5:2<79::aid-bspy2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Structure/activity studies of the anti‐MUC1 monoclonal antibody C595 and synthetic MUC1 mucin‐core‐related peptides and glycopeptides

Abstract: MUC1 mucin is a large complex glycoprotein expressed on normal epithelial cells in humans and overexpressed and under or aberrantly glycosylated on many malignant cancer cells which consequently allows recognition of the protein core by antibodies. In order to understand how glycosylation may modulate or regulate antibody binding of mucin protein core epitopes, we have analyzed the antibody C595 (epitope RPAP) for its structure, stability, and its binding to a series of synthetic peptides and glycopeptides by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…19 The antibody binds specifically and preferentially to differentially glycosylated MUC1 in immunohistochemistry. Thus, although the epitope of the PH1 antibody may fall outside the amino acids that are putatively glycosylated, its binding may still be affected because of steric hindrance or carbohydrate-induced conformational changes of the epitope within the tandem repeat region, as described by Spencer and colleagues 28 for the antibody C595 that binds to the RPAP epitope.…”
Section: Discussionmentioning
confidence: 82%
“…19 The antibody binds specifically and preferentially to differentially glycosylated MUC1 in immunohistochemistry. Thus, although the epitope of the PH1 antibody may fall outside the amino acids that are putatively glycosylated, its binding may still be affected because of steric hindrance or carbohydrate-induced conformational changes of the epitope within the tandem repeat region, as described by Spencer and colleagues 28 for the antibody C595 that binds to the RPAP epitope.…”
Section: Discussionmentioning
confidence: 82%
“…Although SM3 is specific for a glycopeptide, X-ray crystallography and NMR studies revealed that glycosylation was not required for binding, but that the GalNAc O-glycosylation induced conformational changes in the peptide that enhanced its interactions with the antibody (20,34). Similarly, mAb C595 raised against another peptide epitope in MUC1 (sequence RPAP) was found to have enhanced affinity because of conformational changes induced by Tn glycosylation, which was attributed to the stabilizing of a left-handedpolyproline II helix by di-or triglycosylation of the peptide (35).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of the antibody SM3 to the PDTR region of MUC1 has been studied in detail by X-ray crystallography and NMR spectroscopy (Dokurno et al 1998;Moller et al 2002), and GalNAc O-glycosylation of the Thr residue in PDTR induces conformational changes in the peptide region, enhancing antibody interaction with the peptide core, but without siginificant interaction with the GalNAc residue. Similarly, binding of the MAb C595 to the RPAP peptide epitope is enhanced by conformational changes induced by Tn-glycosylation of Thr in VTSA as well as Ser and Thr in GSTA regions (Spencer et al 1999). In contrast, NMR studies of the binding of the antibody B27.29 suggest that the antibody epitope maps to two separate parts of the glycopeptide, with the core peptide epitope spanning the PDTRP sequence and a second carbohydrate epitope comprising Tn-glycans at Thr and Ser in the VTSA region (Grinstead et al 2002).…”
Section: Discussionmentioning
confidence: 99%